Hitman forty years making music, topping charts, & winning Grammys - Foster, David 1949- (Pocket Books, 2008)
After almost four decades in the music business, David Foster--producer, arranger, songwriter, performer--relates his compelling and outspoken memoir, describing the delicate balancing act between artist and producer, offering revealing portraits of some of those artists at work, and sharing his secrets for success in the maddeningly fickle music industry.
Keywords: Foster, David -- 1949-; Sound recording executives and producers -- Biography; Biografie